Challenges of Higher Education Learning and Scientific Research Process Management - Gulua, Ekaterine (European Journal of Multidisciplinary Studies, 2018)
This work is dedicated to the 100th anniversary of the First University of Georgia and aims to find ways to improve management policies of higher education institutions in Georgia. The study was based on the analysis of foreign experience of modern strategies of higher education management, the qualitative analysis of TSU management system and the survey of academic personnel of the university economics and business faculty. Based on the results obtained, the challenges of management and scientific process management are analyzed. Challenges identified in the paper are informative not only at TSU but at other higher educational institutions of Georgia for understanding the conditions there and it will be the basis for the mechanisms of overcoming challenges at higher education institutions and management improvement recommendations.